(3GdCSfi aj eMd GdESQG aj aVGFd GdeSLO GdCbUis - (3CHh GdeYGdj eTQa Hf eQLj Hf EHQGgje GdebOSj, GHf eQLjs ((3EHQGgje NjQ GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdTjSN GdCLd CHhGdeYGdi GdeTQa Hf GdeQLj GdMeO ddg GdPi Ndb GdCQV hGNJGQ efgG ehGVY hQaYgG s
(3BNQgG (B:s
(3fSCd Gddg Cf jfaYfG Hg hMSHfG Gddg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B172 - (3U(B177s
(3HQcdef edMb (B1:567s
(3hSeGg aVGFd HjJ GdebOS hGdTGes
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3LeYs
Keywords: (3GdJGQjNs